Monetary Myopia: An Examination of Institutional Response to Revenue From Monetary Sanctions for Misdemeanors - Martin, Karin D. (Criminal justice policy review, 2018)
Monetary sanctions (fines, fees, surcharges, etc.) are codified in municipal, state, and federal statutes and create an incentive for jurisdictions to shift from using them for punishment to using them for revenue. Misdemeanors are of particular concern because they dominate the court system and provide ample opportunity to assess surcharges on top of punitive fines. This article uses a modified case study to explore how Nevada and Iowa, two different but comparable states, respond to the revenue incentive in misdemeanor convictions. In Nevada, the legislature has increasingly required the courts to become self-funding; in Iowa, the state has responded to monetary incentives by focusing almost exclusively on collections. The analysis reveals a connection between the destination of revenue and the collection apparatus and shows misdemeanor sanctions to be a domain of conflicting goals. The article proposes the concept of “monetary myopia” to explain the states’ behavior.